1982
DOI: 10.1063/1.330926
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostatic wave devices and applications (invited)

Abstract: Microwave magnetics technology is faced with two challenges: the development of an analog signal processing capability directly at microwave frequencies, and development of electronically tunable nanosecond time delays for phased array antennas. The focus is on these two problems from the point of view of magnetostatic wave (MSW) technology in thin films such as liquid phase epitaxy yttrium iron garnet. An assessment is made of MSW devices, their role in realizing wideband phased arrays, and how MSW stacks up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The wavelet transform of signal f (t) is [6][7][8][9][10][11][12][13][14]. When s = 2 k , the wavelet function shown in (3) is converted into the Morlet dyadic wavelet function [6][7][8][9][10][11][12].…”
Section: Implementation Schemes Of a Single-scale Wavelet Transform Pmentioning
confidence: 99%
See 2 more Smart Citations
“…The wavelet transform of signal f (t) is [6][7][8][9][10][11][12][13][14]. When s = 2 k , the wavelet function shown in (3) is converted into the Morlet dyadic wavelet function [6][7][8][9][10][11][12].…”
Section: Implementation Schemes Of a Single-scale Wavelet Transform Pmentioning
confidence: 99%
“…Through analysis and research we found that , as long as the input transducer of MSSW device is designed according to a scale wavelet function shown in the formula (4), a single-scale wavelet transform processor using a MSSW device can be implemented. We know from [6][7][8][9][10][11][12] that a single-scale wavelet transform processor using the Morlet wavelet function can be used as a band-pass filter. When k is 13, the scale s is equal to 1.492 -13 , so the wavelet function for the scale 1.…”
Section: Implementation Schemes Of a Single-scale Wavelet Transform Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Practically, this scheme of delaying feedback can be realized, for example, with the help of delay lines on magnetostatic waves 47,48 or acoustic waves. When the stabilization regime takes place and the system is exactly in the equilibrium state, the feedback signal f fb could by compared with the noise level.…”
Section: Stabilization Of Unstable Equilibrium Spatial State Witmentioning
confidence: 99%
“…This enables engineering of arbitrary band structures for carrier signals in the several-GHz range. These unique properties have been widely used to design passive radio frequency elements, including tunable filters 3 and delay lines 4 . However, the most important feature of SWs is their propagation without charge transport.…”
mentioning
confidence: 99%